Zarys regulacji prawnej w przedmiocie buforów kapitałowych jako narzędzi realizacji celów polityki makroostrożnościowej - Grodecka, Anna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The purpose of this paper is to briefly present current regulatory framework which encompasses four new instruments of macro-prudential policy against efficiency of their application as tools of macro-prudential policy. The framework has been shaped initially by the Basel Committee on Banking Supervision in the form of guidelines included in Basel III that were further developed by provisions of Capital Requirements Directive IV (CRD IV) and Capital Requirements Regulation (CRR). Transposition of legal requirements into polish legislation was concluded by enactment of the Act on macro-prudential oversight of financial system and crisis management within financial system. The Act constituted a step forward in providing national authorities responsible for pursuing objectives of the macro-prudential policy with proper toolkit. Through an analysis of the regulatory framework and consequential obligations imposed onto institutions functioning within the financial system to maintain an additional amount of own funds as capital buffers carried out along with comparison between the current framework and concepts that underpinned it, the author performs an assessment of the regulatory framework highlighting advantages and pointing out concerns for future reference.
Keywords: capital buffers; macro-prudential policy; macro-prudential tools; countercyclical capital buffer; systemic risk